A Web Tool for Calculating Substituent Descriptors Compatible with Hammett Sigma Constants. Issue 12 (30th August 2022) - Ertl, Peter
Abstract: The electron‐donating and ‐accepting power of organic substituents is an important parameter affecting many properties of parent molecules, most notably their reactivity and p K a of ionisable groups. These substituent properties are described by Hammett σ constants obtained by measuring ionization constants of substituted benzoic acids. Although values of the Hammett σ constants have been measured for the most common functional groups, data for many important substituents are not available. In the present study, a method to calculate substituent descriptors compatible with the Hammett σ constants using quantum‐chemically derived parameters is described. On this basis, a free web tool allowing to calculate electronic and hydrophobic substituent descriptors is made available at https://bitly.com/getsigmas . Abstract : A method to calculate substituent descriptors compatible with the Hammett σ constants using quantum chemical parameters is described, and a free web tool allowing to calculate electronic and hydrophobic substituent descriptors is made available at https://bitly.com/getsigmas .